KERJASAMA INTERNATIONAL LABOUR ORGANIZATION (ILO) DAN INDONESIA DALAM MENINGKATKAN KUALITAS USAHA KECIL MENENGAH (UKM) BALI MELALUI PROGRAM SCORE TAHAP III TAHUN 2019 - Alcini Widiasta (2023)
The Indonesian state is still stumbling over a number of problems related to employment such as the problem of limited absorption of the economy which is not in accordance with the number of workforce which is increasing year by year, SMEs are the goal to develop the Indonesian economy and reduce unemployment. This study aims to determine the analysis of cooperation between Indonesia and the International Labor Organization (ILO) in the SCORE Phase III program in improving the quality of SMEs in Bali, with the help of SCORE Program training with several methods and modules in it. Assisted by the Ministry of Manpower. The author uses the theory of International Cooperation as the authority of a region, then takes an approach by bringing an issue to the problem and then conducting problem discussions and creating negotiations to find out the origin of a problem and provide a solution that can satisfy all parties. This research was analyzed using qualitative methods. The results of this research collaboration through the collaboration program of international organizations such as the International Labor Organization (ILO) through a training program specifically designed to provide training for SME readiness, namely SCORE, it is hoped that this collaboration can produce business actors who are ready to develop their potential and compete in the international market.